Kondisi Terkini Presentase Tutupan Terumbu Pada Masa Pandemi Covid-19 di Gili Air, Taman Wisata Perairan Gili Matra, Nusa Tenggara Barat: The Current Condition of the Coral Reef Cover Percentage during the Covid-19 Pandemic in Gili Air, Gili Matra Marine Protected Area, West Nusa Tenggara - Nurliah Buhari; Mahardika Rizqi Himawan; Edwin Jefri; Paryono Paryono; Ibadur Rahman; Ayu Adhita Damayanti (LPPM Universitas Mataram, 2021)
Gili Matra Aquatic Tourism Park has two conservation targets, namely biological targets and social, cultural and economic targets. Coral reef ecosystems, apart from being a conservation target, are also an attraction for tourists to visit. This research was conducted to determine the condition of the coral reef ecosystem to be used as the basis for the management of conservation areas. The research was conducted by collecting coral reef data either through surveys or secondary data from the results of previous studies. Coral reef survey using the standard Line Intercept Transect method. The survey results show that the condition of coral reefs in the utilization zone is better than the core zone. Live coral cover in the utilization zone reached 71% so it was categorized as good, while in the core zone it only reached 8% so it was categorized as bad. Coral reefs in the core zone are unable to recover even though the number of tourists has decreased during the Covid-19 pandemic. Therefore, the location of the core zone on Gili Air needs to be evaluated further so that the effectiveness of Gili Matra TWP management can be improved. Key words: coral reefs; Gili Matra; Conservation